Conceptualizing Soft Power of Higher Education Globalization and Universities in China and the World - Li, Jian (Perspectives on Rethinking and Reforming Education,, 2018)
This book examines the globalization trends in higher education from an international political science perspective, using Nye's theory of soft power to explore the rationale behind it. It focuses on conceptualizing the Soft Power Conversion Model of Higher Education, which is embedded in the globalization of higher education, and analyzes the globalization of Chinese higher education reform. Also, this book provides innovative and unique viewpoints on conceptualizing and mapping the globalization and internationalization of higher education, especially for current Chinese higher education (1949-2016). It discusses and illustrates cutting-edge concepts of global higher education, such as global learning, global competency, and global citizenship and refines them in the conceptualized soft power conversion model of higher education. This book reports on and enriches the theoretical concept of global education, and provides practical insights into global learning, global citizenship and global competency for Chinese undergraduate students.